Neoadjuvant versus Adjuvant Chemotherapy for Resectable Pancreatic Adenocarcinoma: A National Cancer Database Analysis. Issue 9 (September 2018) - Hashmi, Ammar; Kozick, Zachary; Fluck, Marcus; Hunsinger, Marie A.; Wild, Jeffrey; Arora, Tania K.; Shabahang, Mohsen M.; Blansfield, Joseph A.
There is controversy regarding the role of neoadjuvant versus adjuvant chemotherapy for pancreatic cancer (PAC). Neoadjuvant therapy has been touted as a method to improve survival in PAC patients. This study's objective is to investigate predictors and potential benefits of neoadjuvant therapy in resectable PAC patients. The National Cancer Data Base was used to retrospectively analyze stage I and II surgically resected PAC patients receiving adjuvant or neoadjuvant therapy from 2004 to 2012. A total of 12, 983 patients were identified. A significant increase in the rate of neoadjuvant therapy was observed over time with 5 per cent receiving neoadjuvant therapy in 2004 versus 17 per cent in 2012 (P < 0.0001). Multivariate analysis showed that patients were more likely to receive neoadjuvant therapy if they were treated at an academic facility. Private insurance was associated with higher odds of neoadjuvant chemotherapy (P < 0.0001). Pathological outcomes were improved in neoadjuvant patients compared with adjuvant patients on multivariate analysis with neoadjuvant patients having higher rates of negative surgical margins (OR: 1.273, 95% Confidence interval: 1.099–1.474) and negative lymph nodes (OR: 2.852, 95% Confidence interval: 2.547–3.194). Pathological outcomes are improved after neoadjuvant therapy compared with adjuvant therapy, with more patients achieving negative margins and negative lymph nodes. Prospective studies are needed to compare these two treatment modalities in a head to head comparison.